Penyalahgunaan Kewenangan Oleh Oknum Polisi Dalam Kasus Narkoba - Goa, Marselinus (Media Hukum Indonesia (MHI), 2025)
Today, drug crimes are seen as crimes that are the enemy of humanity, therefore countries in the world including Indonesia continue to fight to eradicate this crime. The problems raised in this writing are Abuse of Authority by Police Officers in Drug Cases, how are the regulations and Criminal Sanctions against the Police who commit Drug Crimes, and how to apply criminal sanctions and codes of ethics to the Police as perpetrators of Drug Crimes. This writing uses a Non-Research Method which uses the argumentation method and accumulation of the author's academic critical thoughts. This writing does not use research and empirical. From this research, it can be concluded that 1) The law enforcement process against police officers who are caught in drug abuse cases is in accordance with applicable laws and regulations, where in the process that everyone is the same in the eyes of the law, even in law enforcement where the suspect is a police officer, the sentence can be heavier. This is because the suspect is a law enforcement officer who should be carrying out the office's order to combat narcotics, but the suspect was involved in a narcotics abuse crime case. 2) The process of enforcing the police's professional code of ethics against police officers who are caught in a narcotics abuse crime case has not been implemented properly in reality, where the police do not immediately take firm action against members who are caught in a narcotics abuse crime case, as if the police are still protecting their members and are considered after their members have been tried in a general court and found guilty of committing a narcotics crime.